Model Konseling Perilaku Menggunakan Teknik Manajemen Diri untuk Pengembangan Program Tahfidz: Behavioral Counseling Model Using Self Management Techniques for The Development of The Tahfidz Program - Muhamad Safiul Umam; Ahmad Khotibul Umam; Muh Klasin (Jurnal IKA, 2026)
The Tahfidz Al-Qur’an program plays a crucial role in shaping students’ religious character and discipline; however, its implementation at MTs Mardlatillah Singaraja has not yet reached optimal outcomes. Students face challenges related to motivation, time management, and consistency in memorization, indicating the need for counseling interventions that foster self-regulation. This study aims to develop a behavioral counseling model employing the self-management technique to optimize the Tahfidz training program. The research utilized a Research and Development (R&D) approach with the 4D model (Define, Design, Develop, and Disseminate). The research subjects consisted of seven Tahfidz program students and five expert validators. The validation results revealed a Content Validity Index (CVI) value of 1.00, indicating a very high level of validity and feasibility. The effectiveness test using the Wilcoxon test showed significant improvements in students’ memorization achievement, emotional control, and self-regulation. These findings confirm that the behavioral counseling model with the self-management technique is effective and feasible as a counseling guidance framework to strengthen the Tahfidz program and to develop students’ religious, disciplined, and independent character.